Perceptions and Feedback of Medical Students about the National Medical Commission India Mandated Electives Program - Sujata Sethi; Bhupendra Singh; Prashant Kumar; Rakesh Mittal; Ashuma Sachdeva (CHRISMED Journal of Health and Research, 2024)
Background: Electives program was introduced by the National Medical Council for Phase 3 MBBS students in India as a mandatory 2-month program, to facilitate learning beyond primary care and allow students to plan their careers by providing more choices. Aim: The aim of the study was to assess the relevance and importance of the electives program as perceived by the Phase 3 Part II MBBS students. Materials and Methods: An online study was conducted at the Pt. B. D. Sharma PGIMS, Rohtak, involving 243 MBBS students to collect their perceptions, experiences, and suggestions for further improvement. Results: Eighty percent of 243 participants were satisfied with the method of allocation of electives. Three-fourths of participating students felt that the duration of electives was sufficiently long. Most of the students (79%) enjoyed Block 2 more than Block 1, while 44% of the students did not enjoy either of the elective postings. Ninety percent of participants perceived electives improved their self-directed learning. The novelty of experience and hands-on experience contributed in making learning enjoyable. Various attributes of mentors (availability, attitude, active teaching, and feedback) were considered facilitators of learning while fear of making mistakes and lack of guidance were considered to be hindering forces. The majority of students felt that elective postings helped them to contemplate future career options. Conclusions: Students perceived the timing of the electives as a positive change. The present study highlighted the potential of electives in undergraduate medical curricula by pointing out the possible determinants of students’ satisfaction with electives. Feedback from the maiden year of implementation of electives will help recognize the shortcomings and improve.